Predicting the impact of COVID-19 on Australian universities - Arran Thatcher; Mona Zhang; Hayden Todoroski; Anthony Chau; Joanna Wang; Gang Liang (Journal of Risk and Financial Management, 2020)
This article explores the impact of the novel coronavirus (COVID-19) upon Australia's education industry with a particular focus on universities. With the high dependence that the revenue structures of Australian universities have on international student tuition fees, they are particularly prone to the economic challenges presented by COVID-19. As such, this study considers the impact to total Australian university revenue and employment caused by the significant decline in the number of international students continuing their studies in Australia during the current pandemic. We use a linear regression model calculated from data published by the Australian Government's Department of Education, Skills, and Employment (DESE) to predict the impact of COVID-19 on total Australian university revenue, the number of international student enrolments in Australian universities, and the number of full-time equivalent (FTE) positions at Australian universities. Our results have implications for both policy makers and university decision makers, who should consider the need for revenue diversification in order to reduce the risk exposure of Australian universities.
Keywords: 330; COVID-19; Australian universities; education; full-time equivalent employment; international student enrolment; revenue